The moon over Star - Aston, Dianna Hutts; Pinkney, Jerry (New York : Dial Books for Young Readers, 2008)
On her family's farm in the town of Star, eight-year-old Mae eagerly follows the progress of the 1969 Apollo 11 flight and moon landing and dreams that she might one day be an astronaut, too.
4.8
K-3
Coretta Scott King Award, 2009
Keywords: Apollo 11 (Spacecraft) -- Juvenile fiction; Space flight to the moon -- Juvenile fiction; Farm life -- Juvenile fiction; African Americans -- Juvenile fiction; Apollo 11 (Spacecraft) -- Fiction; Space flight to the moon -- Fiction; Farm life -- Fiction; African Americans -- Fiction; Apollo 11 (Spacecraft) -- Fiction; Space flight to the moon -- Fiction; Farm life -- Fiction; African Americans -- Fiction